Significance Of Pro-Inflammatory Cytokines (Il-8, Ifnγ) In Prediction Of The Course In AD, COPD, and ACO - Fayzullaeva N.Ya; Raufov A.A. (Universitas Muhammadiyah Sidoarjo, 2022)
Asthma and chronic obstructive pulmonary disease (COPD) are a major public health problem and a leading cause of morbidity and mortality worldwide. Asthma and COPD are the most common chronic respiratory diseases, each with a specific pathophysiology. Usually, asthma is characterized by chronic inflammation of the airways with reversible symptoms, while COPD is characterized by persistent respiratory changes in the bronchopulmonary system. The importance of the need for its further study is beyond doubt, since this pathology significantly reduces the quality of life of patients, being a serious medical and social problem.